Implementasi Web-Service dan Aplikasi Seluler Pada Sistem Pemantauan Proses Penjernihan Air Perusahaan Daerah Air Minum - Trias Bratakusuma; Zanuar Rifai; Muhrofin Muhrofin (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2018)
Clean water is a water that can be used for many household need. To produce a high quality water a supervision on its production needs to be done by pdam on a regular basis in order to qualify for the requirements such as physic, microbiology, chemistry, radioactive. This days reporting process that is on time and accurate has yet to be done, beside that there is potential of mistake from this reporting due to its conventional preparation process was still high. The purpose from this was to implement web service using RESTfull method server that are integrated with cellular app in smartphone with android platform so that the data reporting process can be done at the exact same time with serving it on the data sample in a graphic and table form. The data gathering technique that are being used in this research was observation technique, interview, documentation, literature review, and questionnaire. The method that are being used in this research was the Global extreme programming method (GXP). This research produce a supervision on water cleansing based on cellular app based on web service to support the data reporting that are done real time, so the possibility of mistake in the water processing process In PDAM Tirta Wijaya can be known as soon as possible